Article including porous layer containing inorganic particles, and coating liquid for forming porous layer containing inorganic particles
Patent Information
- Application Number
- JP2022070826
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-04-22
- Publication Date
- 2025-04-02
AI Technical Summary
Existing porous films with inorganic particles face cracking issues when thickness exceeds 1.0 μm due to stress during solvent drying, and using epoxy resin as a binder increases the refractive index, compromising low refractive index performance.
A porous layer composed of inorganic particles bound with an inorganic binder, where chain particles constitute 55% to 95% of the total particles, and a coating liquid with a neutral organic solvent containing 30% to 80% hydroxyl group solvents with 4 to 6 carbon atoms is used to suppress cracking and maintain a low refractive index.
The solution enables a crack-free porous layer with a refractive index of 1.3 or less, even at thicknesses up to 5 μm, maintaining excellent scratch resistance and antireflection properties.
Smart Images

Figure 00000000_0001_ABST 
Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to an article having a porous layer containing inorganic particles, and a coating liquid for forming a porous layer containing inorganic particles. [Background technology]
[0002] Porous films containing particles are known to have a low refractive index. By incorporating chain-like or hollow particles to form voids within the film, the refractive index of the entire film can be lowered. A widely used method for forming porous films containing particles is to apply a coating liquid containing particles and dry it.
[0003] In a method for forming a porous film using a coating liquid containing particles, a process of drying the solvent contained in the coating liquid is carried out, which generates stress within the film. When attempting to form a porous film with a thickness of 1.0 μm or more, the stress increases and cracks occur in the porous film. To solve this problem, Patent Document 1 uses a flexible epoxy resin as a binder to bind silicon oxide particles together, thereby achieving a porous film that is less likely to crack even when the film is thick. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2018-145339 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the film of Patent Document 1 contains, as a binder, an epoxy resin having a higher refractive index than silicon oxide, which results in a high overall refractive index, thereby reducing the performance as a low refractive index film. [Means for solving the problem]
[0006] The present invention has been made in view of the above problems, and provides an article having a porous layer in which the occurrence of cracks is suppressed regardless of the film thickness.
[0007] The article of the present invention comprises a substrate and a porous layer provided on the substrate, the porous layer containing a plurality of inorganic particles bound together with an inorganic binder, wherein the plurality of inorganic particles include chain particles and particles other than the chain particles, and the volume ratio of the chain particles to the plurality of inorganic particles is 55% or more and 95% or less.
[0008] The coating liquid according to the present invention is characterized in that it contains a plurality of inorganic particles, a component that serves as an inorganic binder, and an organic solvent, the plurality of inorganic particles including chain particles and particles other than the chain particles, the volume ratio of the chain particles to the plurality of inorganic particles being 55% or more and 95% or less, and 30% by mass or more and 80% by mass or less of the organic solvent being a water-soluble solvent having a hydroxyl group with 4 to 6 carbon atoms. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide an article having a porous layer in which the occurrence of cracks is suppressed regardless of the film thickness. [Brief explanation of the drawings]
[0010] [Figure 1] FIG. 1(a) is a schematic cross-sectional view showing an example of the configuration of an article according to the present invention, and FIG. 1(b) is a partially enlarged view of a porous layer. [Figure 2] 1(a) to 1(c) are schematic diagrams showing modified examples of the article according to the present invention. [Figure 3] FIG. 1 is a diagram showing an example of the configuration of a lens filter, which is an example of an article according to the present invention. [Figure 4] FIG. 1(a) is a diagram showing an example of the configuration of a photoelectric conversion device as an example of an article according to the present invention, and FIG. 1(b) is a diagram showing a modified example. [Figure 5] 1 is a schematic diagram of an imaging device, which is an example of an optical device using an article according to the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0011] After describing the article having a porous layer according to the present invention, a coating liquid for forming the porous layer and a method for forming the porous layer using the same will be described.
[0012] [Article with porous layer] The porous layer of the article according to the present invention has a low refractive index and excellent scratch resistance, and can be made thick. For example, by designing the porosity and thickness of the porous layer within the range necessary to achieve the desired antireflection and / or antifogging properties, various articles can be realized.
[0013] First Embodiment Fig. 1(a) is a schematic diagram showing an example of the configuration of an article 100 according to the present invention. The article 100 in Fig. 1(a) has a substrate 110 and a porous layer 120 containing inorganic particles provided on the substrate 110. The article 100 according to this embodiment is a lens, a mirror, a filter, a functional film, or the like, and the porous layer 120 functions as an anti-reflection film and / or an anti-fogging film, or the like, depending on the design.
[0014] (base material) The material of the substrate 110 may be glass, ceramics, resin, metal, semiconductor, etc. Furthermore, the shape thereof is not limited, and it may be a flat plate, a curved shape with a concave or convex surface, a film, etc. When used for optical purposes, it is preferable to use a light-transmitting substrate having a light transmittance of 90% or more, more preferably 95% or more in the wavelength range of 400 nm to 700 nm.
[0015] The composition of the glass or ceramic is not particularly limited. Examples include zirconium oxide, titanium oxide, tantalum oxide, niobium oxide, hafnium oxide, lanthanum oxide, gadolinium oxide, silicon oxide, calcium oxide, barium oxide, sodium oxide, potassium oxide, boron oxide, and aluminum oxide. The substrate 110 can be produced by known methods such as grinding and polishing, molding, and float forming.
[0016] The resin is preferably a thermoplastic resin or a thermosetting resin. Examples of the thermoplastic resin include polyethylene terephthalate, PET (polyethylene naphthalate), PP (polypropylene), PMMA (polymethyl methacrylate, acrylic resin), triacetyl cellulose, PC (polycarbonate), cycloolefin polymer, and polyvinyl alcohol. Examples of the thermosetting resin include polyimide, epoxy resin, and urethane resin.
[0017] The metal may be made of one type of metal element or an alloy containing two or more types of elements.
[0018] An example of a semiconductor is silicon.
[0019] (porous layer) FIG. 1(b) shows an example of a partially enlarged porous layer 120. The porous layer 120 contains, as a plurality of inorganic particles, chain particles 121 and particles 122 other than the chain particles. The plurality of inorganic particles are bound to one another by an inorganic binder 124, and voids 125 are formed between the inorganic particles. The chain particles refer to secondary particles formed by binding a plurality of solid primary particles together and connecting them in a linear or curved manner.
[0020] In order for the porous layer 120 to function as an anti-reflection film and / or an anti-fogging film, the refractive index is preferably 1.3 or less. If the refractive index exceeds 1.30, the layer contains too few voids, which may result in an insufficient reduction in the refractive index difference between air and the substrate 110, resulting in poor anti-reflection performance, or in a poor moisture absorption capacity, resulting in poor anti-fogging performance. Because it is not possible to reduce the refractive index of the porous layer 120 to the same level as air, which is 1.0, the refractive index of the porous layer 120 is preferably 1.15 to 1.30, more preferably 1.18 to 1.25, and even more preferably 1.18 to 1.23.
[0021] The refractive index of the porous layer 120 can be adjusted by the materials of the inorganic particles and inorganic binder 124 contained in the porous layer 120 and the amount of voids 125 (porosity), and the porosity can be adjusted by the size and shape of the inorganic particles.
[0022] The thickness of the porous layer 120 is designed based on the refractive index (porosity) of the porous layer 120 and the wavelength of light for which reflection is to be prevented or the desired anti-fogging performance. Depending on the application of the article 100, the thickness of the porous layer 120 may need to be 1000 nm or more, and to prevent cracks from occurring even when the thickness is 1000 nm or more, the internal stress of the porous layer 120 must be reduced as much as possible.
[0023] It is believed that the internal stress of the porous layer 120 is likely to occur when the film density of the porous layer 120 becomes too high and when there are unevenness in the film density in the film thickness direction.
[0024] In the present invention, in order to realize a porous layer 120 that is less likely to crack even when the film thickness is increased, the inorganic particles constituting the porous layer 120 contain a predetermined amount of chain particles, and also contain particles other than chain particles, thereby suppressing an increase in the film density of the porous layer 120. Furthermore, the coating liquid for forming the porous layer is devised to suppress unevenness in the film density of the porous layer 120 in the film thickness direction. The coating liquid for forming the porous layer will be described later. Even when using the present invention, if the film thickness of the porous layer 120 exceeds 5000 nm, cracks tend to occur easily. The film thickness of the porous layer 120 of the article according to the present invention is preferably 5000 nm or less, more preferably 3000 nm or less.
[0025] The inorganic particles are particles of an inorganic compound having a refractive index of less than 1.5 in at least a part of the visible light range. Specifically, particles of silicon oxide, magnesium fluoride, lithium fluoride, calcium fluoride, barium fluoride, etc. are preferred, and silicon oxide particles are particularly preferred in view of availability. The composition of the inorganic particles contained in the porous layer can be determined by analyzing a cross section of the porous layer using energy dispersive X-ray analysis (EDX).
[0026] To realize a porous layer 120 that is less likely to crack even when the film thickness is increased, the volume ratio of the chain particles 121 to the inorganic particles contained in the porous layer 20 should be 55% or more and 95% or less. More preferably, it should be 60% or more and 95% or less. The volume ratio of the chain particles 121 to the inorganic particles can be calculated by the following method. A cross section of the porous layer 120 is imaged using a transmission electron microscope, and the ratio of the area occupied by the chain particles 121 to the area occupied by the inorganic particles is calculated in a specified area. This is performed for five or more regions, and the average value is taken as the volume ratio of the chain particles 121 to the inorganic particles. The area of the cross section of the porous layer imaged using a transmission electron microscope is 0.2 μm 2 It is preferable that the ratio is equal to or greater than this. Since this method is an average value of cross-sectional areas at five or more locations, it is possible to obtain a value that is approximately the same as the actual volume ratio, even though it is an area ratio. When the inorganic particles constituting the porous layer 120 include chain particles and particles other than chain particles and the volume ratio of the chain particles is within the above range, chain particles 122 other than chain particles enter between the chain particles 121, causing a moderate disruption of the arrangement of the inorganic particles. As a result, more voids are formed between the inorganic particles than in a porous layer composed of a single particle, preventing the film density from becoming too high and reducing stress generated within the porous layer. A porous layer 120 containing chain particles and particles other than chain particles also has the effect of achieving both a low refractive index and scratch resistance.
[0027] When emphasis is placed on the anti-reflection performance of the porous layer 120, it is preferable that voids be formed to an extent that light scattering does not occur within the layer. The volume ratio of the chain particles 121 to the inorganic particles is preferably 55% or more and 92% or less, and more preferably 60% or more and 90% or less.
[0028] When emphasis is placed on the anti-fogging performance of the porous layer 120, a larger amount of voids contained in the porous layer 120 is preferable because it increases the amount of moisture absorbed. The volume ratio of the chain particles 121 to the inorganic particles is preferably 65% or more and 95% or less, and more preferably 70% or more and 95% or less.
[0029] The primary particles constituting the chain particles may be spherical, cocoon-shaped, or bale-shaped, but the cocoon-shaped or bale-shaped form is particularly preferred, and particles with a minor axis of 8 nm or more and 20 nm or less and a major axis of 1.5 times or more and 3.0 times or less the minor axis are particularly preferred.
[0030] The thickness of the chain particles corresponds to the average particle diameter d of a single primary particle, which can be determined by calculating the Feret diameters of multiple primary particles from an image of the cross section of the porous layer taken with a transmission electron microscope and averaging them.
[0031] The average particle diameter d of the primary particles is preferably 8 nm or more and 20 nm or less. If the average particle diameter d is less than 8 nm, the surface area of the voids in the porous layer formed by the particles will be too large, which may allow moisture or chemicals from the atmosphere to be absorbed, changing the optical properties of the porous layer. If the average particle diameter exceeds 20 nm, the dispersion of the chain particles in the solvent in the coating liquid that forms the porous layer will become unstable, resulting in poor coatability and the possibility of not obtaining a porous layer with uniform physical properties.
[0032] The average particle size of the chain particles is preferably 3 to 10 times, and more preferably 4 to 8 times, the average particle size of the primary particles. If the average particle size of the chain particles is less than 3 times the average particle size of the primary particles, the amount of voids formed between the inorganic particles will be reduced, and the refractive index may not be sufficiently reduced. If the average particle size of the chain particles is more than 10 times the average particle size of the primary particles, the average void size will be too large, causing light scattering and potentially impairing translucency. Furthermore, the viscosity of the coating liquid will increase, resulting in poor coatability and leveling properties. The average void size here refers to the average diameter of voids formed by the connection of voids formed between inorganic particles, and can be determined by the known nitrogen gas adsorption method.
[0033] The average particle size of the chain particles corresponds to the Feret diameter of the secondary particles, and can be determined by calculating the Feret diameters of at least 50 or more chain particles from a transmission electron microscope image and taking the average value.
[0034] 1(b) is an example in which the porous layer 120 contains hollow particles as the particles other than chain particles 122. When the particles other than chain particles 122 are hollow particles, the porous layer 120 can contain voids in addition to the voids formed between the particles, which is particularly preferable because it makes it easier to reduce the refractive index.
[0035] The particles 122 other than chain particles may be hollow particles or may have a shape other than a chain, such as a cocoon shape, a sphere shape, a disk shape, a rod shape, a needle shape, or a square shape. The particles 122 other than chain particles do not need to be of one type, and a combination of multiple types of particles can be used. The more types of particles 122 other than chain particles contained in the porous layer 120, the more voids can be formed between the inorganic particles, and the more the internal stress of the porous layer 120 can be alleviated.
[0036] The average particle diameter of the hollow particles is preferably 15 nm to 300 nm, more preferably 30 nm to 80 nm. If the average particle diameter is less than 15 nm, it is difficult to stably produce the particles. If the average particle diameter exceeds 300 nm, large voids tend to occur between the particles, which tends to cause scattering by the inorganic particles.
[0037] The average particle diameter of the hollow particles is the Feret diameter. This Feret diameter can be measured by image processing of the images of the hollow particles contained in the porous layer 120 obtained by a transmission electron microscope. As an image processing method, a commercially available image processing software such as ImageJ (manufactured by NIH) can be used. In a predetermined image area, the contrast can be appropriately adjusted as necessary, and the Feret diameter of each particle can be measured by particle measurement, and the average value of multiple particles can be calculated.
[0038] The shell thickness of hollow particles is 10% to 50% of the average particle diameter, preferably 20% to 35%. If the shell thickness is less than 10%, the strength of the particles themselves will be insufficient. If the shell thickness is more than 50%, the ratio of voids to the volume occupied by the particles will be small, reducing the effect of lowering the refractive index. The shell thickness of hollow particles can be measured from a transmission electron microscope image.
[0039] When the particles 122 other than chain particles are solid particles, the average particle diameter is preferably 10 nm to 300 nm, more preferably 10 nm to 150 nm, and even more preferably 10 nm to 100 nm. If the average particle diameter is less than 10 nm, the effect of alleviating the internal stress of the porous layer 120 is reduced, and if the average particle diameter exceeds 300 nm, scattering increases. The average particle diameter of solid particles can be measured as the average Feret diameter of multiple particles, as with hollow particles.
[0040] The inorganic binder 124 that binds the inorganic particles together is preferably an inorganic material of the same quality as the inorganic particles. Using an inorganic material of the same quality as the inorganic particles increases the affinity between the materials, and a strong binding force can be obtained with a small amount. As a result, a lower refractive index can be achieved than when using a resin binder.
[0041] When the chain particles 121 and the chain particles other than the chain particles 122 are silicon oxide particles, a silicon oxide compound is preferably used as the inorganic binder 124. A preferred example of the silicon oxide compound is a cured product of a silicon oxide oligomer obtained by hydrolyzing and condensing a silicate ester.
[0042] The content of inorganic binder 124 in the porous layer is preferably 0.2 parts by mass or more and 20 parts by mass or less of the total inorganic components, more preferably 1 part by mass or more and 10 parts by mass or less. If the content of inorganic binder 124 is less than 0.2 parts by mass relative to the inorganic particles, the bonding between the inorganic particles will be weak, resulting in a film with low scratch resistance. Furthermore, if the content of inorganic binder 124 is more than 20 parts by mass, when forming porous layer 120, the inorganic binder component in the coating liquid will tend to disrupt the arrangement of the inorganic particles, worsening the scattering of visible light in the resulting film and increasing the refractive index.
[0043] Modifications of the article 100 of FIG. 1(a) are shown in FIGS. 2(a) to 2(c). If necessary, as shown in FIG. 2(a), a functional layer 130 such as an antifouling layer or a hydrophilic layer may be provided on the surface of the porous layer 120 opposite the substrate 110. Examples of the antifouling layer include a layer containing a fluoropolymer, a fluorosilane monolayer, and a layer containing titanium oxide particles. The hydrophilic layer is preferably a hydrophilic polymer layer, and particularly preferably a layer containing a polymer having a zwitterionic hydrophilic group such as a sulfobetaine group, a carbobetaine group, or a phosphorcholine group.
[0044] 2(b), an intermediate layer 140 may be provided between the substrate 110 and the particle-containing porous layer 120. By providing the intermediate layer 140, it is possible to suppress the diffusion of impurities from the substrate 110 to the porous layer 120 and to improve the anti-reflection performance of the article 100. The material of the intermediate layer 140 may be selected depending on the purpose, and examples include an inorganic compound layer such as an oxide or nitride layer, and a polymer layer. The intermediate layer 140 may be a single layer of these, or a laminate in which multiple types of layers are stacked.
[0045] The intermediate layer 140 for enhancing the anti-reflection performance of the article 100 is preferably a laminate in which high-refractive-index layers with relatively high refractive indexes and low-refractive-index layers with relatively low refractive indexes are alternately stacked. The high-refractive-index layer preferably has a refractive index of 1.4 or higher, and is preferably a layer containing one selected from the group consisting of zirconium oxide, titanium oxide, tantalum oxide, niobium oxide, and hafnium oxide. The low-refractive-index layer preferably has a refractive index of less than 1.4, and is preferably a layer containing one selected from the group consisting of silicon oxide and magnesium fluoride. The intermediate layer 140 is not limited to being flat, and may also have an irregularity. An intermediate layer 140 with irregularities may also be configured by providing a polymer layer in which columnar or pyramidal projections or depressions are periodically arranged in a secondary pattern, which can enhance the anti-reflection performance.
[0046] As shown in FIG. 2(c), a functional layer 130 and an intermediate layer 140 may be provided in combination.
[0047] When the article 100 is used as a light-transmitting optical article, the average transmittance of the porous layer 120 in the wavelength range of 400 nm to 700 nm is preferably 90.0% or more, more preferably 95.0%, and even more preferably 99.0% or more. If the average transmittance is less than 90.0%, the light transmission is insufficient and the porous layer 120 is not suitable for optical applications. The thickness of the porous layer 120 is preferably 300 nm to 5000 nm.
[0048] Furthermore, since the thickness of the porous layer 120 can be increased, a specific example of the article 100 according to the present invention is a lens filter that requires anti-fogging properties. In addition to anti-fogging properties, lens filters are also endowed with functions such as protecting the lens and imparting effects such as softening, color change, polarization, and dimming to the resulting image depending on the performance of the substrate used. Figure 3 shows an example of the configuration of a lens filter.
[0049] The lens filter 300 has a structure in which a filter article 302 having the configuration shown in Figures 1 or 2 is fitted into a frame 301 provided with an attachment section 303, such as a screw thread or bayonet mount, for attachment to the housing of an interchangeable lens. The filter article 302 has a porous layer 120 on the surface of the frame 301 on which the attachment section 303 is provided, so that when the lens filter 300 is attached to the housing of an interchangeable lens, the porous layer 120 is located on the opposite side to the light incident surface (inside the housing). When exposed to a sudden temperature change, moisture within the housing is absorbed into the pores of the porous layer 120, preventing the lens filter from fogging up.
[0050] [Coating fluid] Next, the coating liquid for forming the porous layer 120 will be described.
[0051] The coating liquid contains a plurality of inorganic particles constituting the porous layer, a component that serves as an inorganic binder, and an organic solvent, and the plurality of inorganic particles include chain particles and particles other than the chain particles, and the volume ratio of the chain particles to the plurality of inorganic particles is 55% or more and 95% or less. Hereinafter, explanations of points that overlap with matters already explained may be omitted.
[0052] (Inorganic particles) The coating liquid contains a plurality of inorganic particles, and the plurality of inorganic particles includes chain particles 121 and particles 122 other than chain particles.
[0053] The thickness of the chain particles 121 corresponds to the average particle diameter d of one primary particle, and is preferably 8 nm or more and 20 nm or less. The average particle diameter d of one primary particle of the chain particles in the coating liquid can be calculated from the specific surface area of the chain particles extracted from the coating liquid. Specifically, the chain particles alone are extracted from the coating liquid, washed, and then dried, and their specific surface area S is measured using a nitrogen adsorption method. The specific surface area S can then be calculated from the particle density ρ and the following formula (1). d=6 / S·ρ···(1)
[0054] The average particle diameter of the chain particles 121 corresponds to the Feret's diameter of the secondary particles, and can be determined by applying a particle dispersion to a substrate, vacuum drying, and then examining an image obtained with a transmission electron microscope. As mentioned above, the average particle diameter is preferably 3 to 10 times, and more preferably 4 to 8 times, the average particle diameter of the primary particles. If the average particle diameter of the primary particles of the chain particles 121 exceeds 10 times, the viscosity of the coating liquid increases, which may result in poor coating properties and leveling properties.
[0055] The particles 122 other than chain particles contained in the coating liquid are non-chain particles such as hollow particles, cocoon-shaped particles, spherical particles, disc-shaped particles, rod-shaped particles, needle-shaped particles, and angular particles. When the particles other than chain particles are hollow particles, the average particle diameter (Feret's diameter) of the hollow particles contained in the coating liquid can be measured by image processing of a transmission electron microscope image, similar to the hollow particles contained in the porous layer 120. The average particle diameter of the hollow particles is preferably 15 nm or more and 300 nm or less, and more preferably 30 nm or more and 80 nm or less.
[0056] When the particles 122 other than chain particles are solid particles, the average particle diameter (Ferret diameter) of the particles in the coating liquid can be determined by dynamic light scattering. The average particle diameter of the solid particles is preferably 10 nm or more and 300 nm or less, more preferably 10 nm or more and 150 nm or less, and even more preferably 10 nm or more and 100 nm or less.
[0057] To form a porous layer 120 that is less likely to crack even when the film thickness is increased, the volume ratio of the chain particles 121 to the inorganic particles contained in the coating liquid should be 55% or more and 95% or less, and more preferably 60% or more and 95% or less. The ratio of the chain particles 121 to the inorganic particles can be determined by imaging the coating liquid or inorganic particles extracted from the coating liquid and dried using a transmission electron microscope, scanning electron microscope, or the like, and calculating the ratio of the area occupied by the chain particles 121 to the area occupied by the inorganic particles.
[0058] By including chain particles in the above proportion of inorganic particles in the coating liquid and also including particles other than chain particles, particles 122 other than chain particles enter between chain particles 121, causing the arrangement of the inorganic particles to be moderately disrupted and forming voids between the inorganic particles. As a result, the film density is prevented from becoming too high, and stress generated within the porous layer can be reduced.
[0059] (Component that acts as an inorganic binder) The inorganic binder 124 that binds the inorganic particles together is preferably an inorganic material of the same quality as the inorganic particles. When silicon oxide particles are used as the chain particles 121 and the particles other than chain particles 122, the component that becomes the inorganic binder is preferably a silicon oxide compound. A preferred example of the silicon oxide compound is a silicon oxide oligomer obtained by hydrolyzing and condensing a silicate ester.
[0060] Silicon oxide particles naturally have silanol (Si-OH) groups on their surfaces, but by mixing them with silicon oxide oligomers in the coating solution, the number of silanol groups on the surface can be further increased. As a result, the surface of the inorganic particles can be made more susceptible to adhesion. When the coating solution is applied and dried, multiple inorganic particles are bound to each other by the cured silicon oxide oligomer, creating a highly scratch-resistant film.
[0061] In the coating solution of the present invention, the content of the inorganic binder component is preferably 0.2 to 20 parts by mass, more preferably 1 to 10 parts by mass, relative to the solute (solid component) contained in the coating solution. If the content of the inorganic binder component is less than 0.2 parts by mass relative to the inorganic particles, the bonding between the inorganic particles will be weak, resulting in a film with low scratch resistance. If the content of the inorganic binder component is more than 20 parts by mass relative to the inorganic particles, the inorganic binder will disrupt the particle arrangement, which will tend to worsen the scattering of visible light in the resulting film and increase the refractive index.
[0062] (organic solvent) If the inorganic particles, i.e., the chain particles 121 and the non-chain particles 2 122, are uniformly dispersed in the coating liquid, a coating film in which each particle is uniformly distributed can be formed on the substrate, and stress generated in the film after drying can be alleviated. Conversely, if the inorganic particles are present in an aggregated state in the coating liquid, the aggregated inorganic particles will be applied to the substrate, which will deteriorate the alignment and generate large stress in the porous layer.
[0063] Any solvent can be used in the coating solution as long as it does not precipitate inorganic particles or cause a sudden increase in viscosity. Examples of suitable organic solvents include: monohydric alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methylpropanol, 1-pentanol, 2-pentanol, cyclopentanol, 2-methylbutanol, 3-methylbutanol, 1-hexanol, 2-hexanol, 3-hexanol, 4-methyl-2-pentanol, 2-methyl-1-pentanol, 2-ethylbutanol, 2,4-dimethyl-3-pentanol, 3-ethylbutanol, 1-heptanol, 2-heptanol, 1-octanol, and 2-octanol; and dihydric or higher alcohols such as ethylene glycol and triethylene glycol. Ether alcohols such as methoxyethanol, ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-propoxy-2-propanol, and 3-methoxy-1-butanol; ethers such as dimethoxyethane, diglyme (diethylene glycol dimethyl ether), tetrahydrofuran, dioxane, diisopropyl ether, dibutyl ether, and cyclopentyl methyl ether; esters such as ethyl formate, ethyl acetate, n-butyl acetate, methyl lactate, ethyl lactate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, and propylene glycol monomethyl ether acetate; various aliphatic or alicyclic hydrocarbons such as n-hexane, n-octane, cyclohexane, cyclopentane, and cyclooctane; and various aromatic hydrocarbons such as toluene, xylene, and ethylbenzene. Various ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc. Various chlorinated hydrocarbons such as chloroform, methylene chloride, carbon tetrachloride, tetrachloroethane, etc. Aprotic polar solvents such as N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene carbonate, etc.Two or more of these solvents may be mixed and used.
[0064] In a coating film formed by applying a coating liquid, the solvent evaporates from the surface opposite the substrate, causing the inorganic particles to bond together and align on the substrate. Therefore, the alignment of the inorganic particles in the porous layer is affected by the drying rate of the solvent. Therefore, the greater the amount of coating liquid applied, i.e., the thicker the porous layer, the greater the difference in drying rate between the side of the coating film closest to the substrate and the side farther from the substrate, which is likely to result in a difference in film density across the thickness. Specifically, the film density of the porous layer 120 is higher on the side closer to the substrate and lower on the side farther from the substrate. This difference in film density across the thickness of the porous layer 120 generates internal stress, which can cause cracks.
[0065] The difference in film density in the thickness direction of the porous layer manifests as a difference in the refractive index in the thickness direction of the porous layer. To prevent cracking of a porous layer disposed on a flat surface of a substrate, the difference in refractive index between the region of the porous layer 120 closer to the substrate than halfway through the film thickness and the region of the porous layer 120 farther from the substrate than halfway through the film thickness is preferably 0.01 or less. It is more preferably 0.005 or less, and even more preferably 0.003 or less. The film thickness of the porous layer 120 is the average film thickness measured at 10 or more locations on the porous layer 120.
[0066] Slowing the drying speed of the coating liquid allows the unbound inorganic particles to be rearranged in the coating liquid to match the arrangement of the previously bound inorganic particles, thereby reducing unevenness in the orientation of the inorganic particles in the film thickness direction. Therefore, to achieve a thick, crack-free porous layer, it is desirable to disperse chain particles 121 and non-chain particles 122 in the coating liquid and to arrange these inorganic particles evenly by slowing the drying speed as much as possible during the drying process after coating.
[0067] From the viewpoint of slowing the drying rate and achieving both the dispersibility of inorganic particles and the coatability of the coating liquid, 30% to 80% by mass of the solvent contained in the coating liquid according to the present invention is a water-soluble solvent having a hydroxyl group having from 4 to 6 carbon atoms. More preferably, 30% to 70% by mass, and even more preferably 30% to 60% by mass, of the solvent contained in the coating liquid is a water-soluble solvent having a hydroxyl group having from 4 to 6 carbon atoms. Water-soluble solvents having a hydroxyl group having from 4 to 6 carbon atoms have a high boiling point compared to organic solvents, and therefore can slow the drying rate of the coating liquid and provide the time required for the inorganic particles in the coating liquid to be uniformly aligned. If the water-soluble solvent having a hydroxyl group having from 4 to 6 carbon atoms contained in the coating liquid is less than 30% by mass of the solvent, it is difficult to achieve a refractive index difference of 0.01 or less between the side closer to the substrate and the side farther from the substrate in a porous layer 120 having a film thickness of 1000 nm or more. If the water-soluble solvent having a hydroxyl group with 4 to 6 carbon atoms exceeds 80% by mass of the solvent, the arrangement of the inorganic particles may become too dense, resulting in a refractive index exceeding 1.3.
[0068] The water-soluble solvent having a hydroxyl group and having from 4 to 6 carbon atoms particularly preferably contains at least one solvent selected from the group consisting of ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, 1-ethoxy-2-propanol, ethyl lactate, and 3-methoxy-1-butanol.
[0069] [Method of manufacturing an article having a porous layer] The method for producing an article having a porous layer according to the present invention includes the steps of applying the above-described coating liquid onto a substrate and drying and / or baking the substrate to which the coating liquid has been applied.
[0070] Methods for applying the coating liquid to the substrate include spin coating, blade coating, roll coating, slit coating, printing, gravure coating, dip coating, etc. When producing an article having a three-dimensionally complex shape such as a concave surface, spin coating is preferred because it is easy to apply the coating with a uniform thickness.
[0071] The drying and / or curing step is a step of removing the organic solvent and bonding the inorganic particles together without disturbing their alignment to form a porous layer. The drying and / or curing step depends on the heat resistance temperature of the substrate, but is preferably carried out at a temperature of 20°C to 200°C. The drying and / or curing step may be carried out for any time that does not affect the substrate and is long enough to remove the organic solvent from the layer, but is preferably 5 minutes to 200 hours, more preferably 30 minutes to 24 hours. Methods for drying and / or curing include methods using an oven or a hot plate.
[0072] <Second embodiment> FIG. 4(a) shows a cross-sectional view of a photoelectric conversion device 400, which is another example of an article according to the present invention.
[0073] The photoelectric conversion device 400 has a photoelectric conversion substrate 403 having a photoelectric conversion unit 401 and a microlens array 402, a light-transmitting plate 404, and a porous layer 405. A solid (porous layer 405) having a refractive index relatively lower than that of the microlenses is disposed between the microlens array 402 and the light-transmitting plate 404, forming a cavity-less structure.
[0074] Porous layer 405 is disposed between microlens array 402 and light-transmitting plate 404, and has a surface that follows the irregularities of microlens array 402 and a surface that follows light-transmitting plate 404. Microlens array 402 is formed by a plurality of microlenses arranged two-dimensionally, and each microlens has a width of, for example, 0.5 μm to 10 μm and a height of, for example, 0.3 μm to 3 μm. Therefore, the difference in height between the irregularities of microlens array 402 is, for example, 0.3 μm to 3 μm.
[0075] The photoelectric conversion device 400 has a cavity-less structure, and therefore has superior mechanical strength to a cavity structure in which the space between the photoelectric conversion substrate 403 and the light-transmitting plate 404 is hollow.
[0076] In the photoelectric conversion device 400, light incident from the outside passes through the light-transmitting plate 404 and the porous layer 405, is collected by the microlens, enters the photoelectric conversion section 401, and is converted into an electrical signal.
[0077] In order for light incident from the outside to be refracted at the interface between the porous layer 405 and the microlens array 402 and enter the photoelectric conversion section 401, the refractive index of the porous layer 405 must be lower than the refractive index of the microlenses that make up the microlens array 402.
[0078] Microlens array 402 is formed from inorganic materials such as silicon oxide, titanium oxide, niobium oxide, zirconium oxide, tantalum oxide, silicon nitride, silicon oxynitride, etc., or resin materials such as acrylic resin, epoxy resin, polyimide resin, styrene resin, etc. Therefore, since the refractive index of a typical microlens is 1.40 to 2.10, the refractive index of porous layer 405 is adjusted to be less than 1.4.
[0079] To improve the light-collecting ability of the microlens, it is preferable to increase the difference in refractive index between the porous layer 405 and the microlens. The refractive index of the porous layer 405 is preferably 1.15 or more and 1.30 or less, more preferably 1.18 or more and 1.25 or less, and even more preferably 1.18 or more and 1.23 or less. When the refractive index of the porous layer 405 exceeds 1.30, for example, when a microlens made of a resin composition having a refractive index of 1.50 to 1.60 is used, the difference in refractive index between the porous layer 405 and the microlens is small, and the light-collecting ability of the microlens decreases.
[0080] From the viewpoint of light transmission through the porous layer 405, if the average transmittance of light in the wavelength range of 400 nm to 700 nm (hereinafter also referred to as transmittance) is 90.0% or more, the porous layer 405 can be called a light-transmitting film. In the photovoltaic device 400, if the average transmittance of light in the wavelength range of 400 nm to 700 nm of the porous layer 405 suitable as a light-transmitting film is 98.5% or more, the performance of the photovoltaic device can be improved. The transmittance of the porous layer 405 is preferably 99.0% or more, more preferably 99.2% or more, and even more preferably 99.4% or more. On the other hand, the transmittance of the porous layer 5 is preferably 100.0% or less, and more preferably 99.9% or less.
[0081] The above numerical ranges can be combined in any manner.
[0082] Unless otherwise specified, the transmittance refers to the transmittance of parallel transmitted light and does not include the transmittance of diffuse transmitted light.
[0083] The thickness of the porous layer 405 is 300 nm to 5000 nm.
[0084] The thickness of porous layer 405 is preferably 800 nm to 5000 nm, more preferably 1000 nm to 5000 nm, even more preferably 1200 nm to 5000 nm, and particularly preferably 1500 nm to 5000 nm. The thickness of porous layer 405 may be 2000 nm or less. The thickness of porous layer 405 may be, for example, 500 nm to 2000 nm, 800 nm to 2000 nm, 1000 nm to 2000 nm, 1200 nm to 2000 nm, or 1500 nm to 2000 nm.
[0085] Porous layer 405 is disposed so as to completely cover microlens array 402, but if the thickness of porous layer 405 is less than 300 nm, it is difficult to completely cover the microlenses, and the apexes of the microlenses may be exposed from porous layer 405. On the other hand, if the thickness of porous layer 405 exceeds 5000 nm, cracks may easily occur in porous layer 405, and transmittance may decrease.
[0086] Here, the film thickness of the porous layer 405 refers to the thickness of the porous layer 405 at its thickest point in the direction perpendicular to the main surface of the light-transmitting plate 404. Specifically, it refers to the thickness of the porous layer 405 at the valley portions of the microlens array 402.
[0087] The surface of the porous layer 405 facing the light-transmitting plate is preferably flatter than the surface of the porous layer 405 facing the microlens array. That is, the surface of the porous layer 405 facing the light-transmitting plate is preferably flatter than the surface of the porous layer 405 facing the microlens array (hereinafter simply referred to as the "lower surface").
[0088] Here, the lower surface of porous layer 405 refers to the uneven surface of porous layer 405 that has unevenness corresponding to the unevenness of microlens array 402. In other words, preferably, the unevenness of the upper surface of porous layer 405 along light-transmitting plate 404 is flatter than the unevenness of the lower surface of porous layer 405. From this perspective, porous layer 405 can be called a planarizing film that flattens the unevenness of microlens array 402.
[0089] When porous layer 405 is used as a planarization film in this way, the thickness of porous layer 405 is preferably 1.5 times or more, and more preferably 3 times or more, the height difference of the unevenness of microlens array 402. The thickness of porous layer 405 may be 5 times or less the height difference of the unevenness of microlens array 402.
[0090] Specifically, the height difference of the upper surface of the porous layer 405 is preferably 500 nm or less, more preferably 200 nm or less, and even more preferably 100 nm or less. If the height difference of the surface is greater than 500 nm, the unevenness on the surface may scatter light, reducing transmittance. Furthermore, a space is formed at the interface between the light-transmitting plate 404 and the porous layer 405, and moisture may penetrate into the porous layer 405 through this space, changing the refractive index or transmittance of the porous layer 405 and reducing the possibility of a decrease in the performance of the photoelectric conversion device.
[0091] 4(b) is a cross-sectional view showing another example of the configuration of the photoelectric conversion device 400. An adhesive layer 408 made of resin is disposed between the porous layer 405 and the light-transmitting plate 404, and bonds the porous layer 405 and the light-transmitting plate 404 to each other. An anti-reflection layer 407 may be disposed between the porous layer 405 and the adhesive layer 408, if necessary. An anti-reflection layer 406 may be disposed between the porous layer 405 and the microlens array 402, if necessary.
[0092] The upper and lower surfaces of antireflection layer 406 have unevenness corresponding to the unevenness of microlens array 402. Antireflection layers 406 and 407 may be thinner than porous layer 405, and the thickness of antireflection layers 406 and 407 may be ¼ or less of the thickness of porous layer 405.
[0093] <Third embodiment> As an example of an optical device that includes an article according to the present invention, a configuration example of an imaging device that includes a lens barrel (interchangeable lens) is shown in Fig. 5. Fig. 5 shows a single-lens reflex digital camera to which the lens barrel (interchangeable lens) is coupled.
[0094] In the present invention, optical equipment refers to equipment equipped with an optical system, such as binoculars, microscopes, semiconductor exposure devices, and interchangeable lenses.
[0095] Furthermore, the imaging device of the present invention refers to imaging devices such as digital still cameras and digital video cameras, imaging systems such as robots and drones equipped with such imaging devices, mobile phones, and other electronic devices equipped with an imaging element that receives light that has passed through an optical element. Note that a modular form, such as a camera module, installed in an electronic device may also be considered an imaging device.
[0096] In FIG. 3, a camera body 502 and a lens barrel 501, which is an optical device, are coupled together, and the lens barrel 501 is a so-called interchangeable lens that can be attached to and detached from the camera body 502.
[0097] Light from a subject passes through an optical system including multiple lenses 503 and 505 arranged on the optical axis of the photographic optical system inside housing 520 of lens barrel 501, and is received by an image sensor. The article according to the present invention can be used for the lenses and image sensor that make up the optical system.
[0098] The lens 505 is supported by an inner tube 504 and is movably supported relative to the outer tube of the lens barrel 501 for focusing and zooming. During the observation period before shooting, light from the subject is reflected by a primary mirror 507 inside the camera body 502, passes through a prism 511, and then is projected to the photographer through a viewfinder lens 512 as a captured image. The primary mirror 507 is, for example, a half mirror, and light passing through the primary mirror is reflected by a secondary mirror 508 toward an AF (autofocus) unit 513. This reflected light is used, for example, for distance measurement. The primary mirror 507 is attached and supported by a primary mirror holder 540, for example, by adhesive. During shooting, a drive mechanism (not shown) moves the primary mirror 507 and secondary mirror 508 out of the optical path, opens a shutter 509, and focuses a captured light image incident from the lens barrel 501 onto an image sensor 510. The aperture 506 is configured to change the aperture area to adjust the brightness and depth of focus during shooting.
[0099] A lens filter 550 is attached to the outermost part of the optical system, that is, at the position of lens barrel 501 furthest from camera body 502 .
[0100] For example, the lens filter 550 may have the configuration shown in FIG. 4, and the image sensor 510 may have the photoelectric conversion device 400 shown in FIG. [Example]
[0101] In Examples 1 to 18, a coating liquid for forming the porous layer 120 was prepared by the following method, and a porous layer was formed on a substrate to produce an article 100 having the porous layer 120. At this time, the coating liquid and the obtained porous layer 120 were evaluated as follows.
[0102] <Evaluation of refractive index of porous layer> A particle-containing porous layer 120 was formed on the polished surface of a glass substrate (30 mm diameter, 1 mm thick synthetic quartz with one side polished) and on a silicon wafer. A spectroscopic ellipsometer (VASE, manufactured by J.A. Woollam Japan) was used to illuminate the porous layer 120 and measure the reflected light from wavelengths of 380 nm to 800 nm to calculate the refractive index. The refractive index at a wavelength of 550 nm was evaluated according to the following criteria. Porous layers rated A or B are suitable as low-refractive-index layers. A: 1.23 or less B: Over 1.23 and 1.30 or less C: Over 1.30
[0103] The surface of the porous layer 120 that is half the average film thickness was divided into a region on the substrate side and a region on the opposite side of the substrate, and the refractive index of each region was evaluated using the method described above. Specifically, an optical model was created assuming that the porous layer 120 has a two-layer structure with a thickness of half the average film thickness of the porous layer 120, and the refractive index of each region was calculated by fitting to the refractive index of the porous layer 120 measured using a spectroscopic ellipsometer.
[0104] The difference in refractive index between the region on the substrate side and the region on the opposite side of the substrate was calculated as the difference in refractive index in the film thickness direction, and the film was evaluated according to the following criteria: If the evaluation was A or B, a porous layer with a sufficiently small difference in film density was obtained. A: 0.003 or less B: Over 0.003 and 0.01 or less C: More than 0.01
[0105] <Evaluation of cracks in porous layers> The surface of the porous layer opposite to the substrate was observed at 300x magnification using a digital microscope (VHX-5000, Keyence) to evaluate the presence or absence of cracks.
[0106] <Evaluation of the thickness of the porous layer> The cross section of the formed porous layer was observed with a scanning electron microscope, measurements were taken at multiple points, and the average value was calculated to determine the film thickness.
[0107] [Example 1] 1-Propoxy-2-propanol was added to 400 g of an isopropyl alcohol dispersion of chain silicon oxide particles (IPA-ST-UP, manufactured by Nissan Chemical Industries, Ltd., particle size 40 nm, solids concentration 15%), while the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solids concentration reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of chain silicon oxide particles (hereinafter referred to as solvent displacement solution 1). The isopropyl alcohol dispersion of hollow silicon oxide particles was added to the obtained solvent displacement solution 1 so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 19:1, to obtain dispersion solution 1. For the isopropyl alcohol dispersion of hollow silicon oxide particles, Sururia 4110 (average particle size approximately 60 nm, shell thickness approximately 10 nm, solids concentration 20.5 mass %) manufactured by JGC Catalysts and Chemicals Co., Ltd. was used.
[0108] In a separate container, 12.48 g of ethyl silicate was added to 13.82 g of ethanol and an aqueous nitric acid solution (concentration 3%), and the mixture was stirred at room temperature for 10 hours to prepare Silica Sol 1 (solid concentration 11.5% by mass). It was confirmed by gas chromatography that the raw material ethyl silicate had completely reacted.
[0109] Dispersion liquid 1 was diluted with ethyl lactate to a solids concentration of 20.0% by mass, and then silica sol 1 was added to the mixture so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 1 containing chain silicon oxide particles and hollow silicon oxide particles.
[0110] The obtained coating liquid 1 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.4 µm.
[0111] [Example 2] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to the solvent replacement liquid 1 so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 9:1, to obtain dispersion 2. As the isopropyl alcohol dispersion of hollow silicon oxide particles, Surulia 4110 (average particle diameter: approximately 60 nm, shell thickness: approximately 10 nm, solid content concentration: 20.5 mass%) manufactured by JGC Catalysts and Chemicals Co., Ltd. was used.
[0112] Dispersion liquid 2 was diluted with ethyl lactate to a solids concentration of 20.0% by mass, and then silica sol 1 was added thereto so that the silicon oxide particles:silica sol ratio was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 2 containing chain silicon oxide particles and hollow silicon oxide particles.
[0113] The obtained coating liquid 2 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.5 µm.
[0114] [Example 3] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 320 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 4:1. Furthermore, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 2). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter approximately 60 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0115] After diluting the solvent displacement liquid 2 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 3 containing chain silicon oxide particles and hollow silicon oxide particles.
[0116] The obtained coating liquid 3 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.7 µm.
[0117] [Example 4] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 320 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 16:3. Then, a propylene glycol monomethyl ether dispersion of solid silicon oxide particles was added so that the mass ratio of chain silicon oxide particles to solid silicon oxide particles was 16:1. While adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0% by mass, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 3). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. The hollow silicon oxide particle isopropyl alcohol dispersion liquid was prepared using Surulia 4110 (average particle diameter: approximately 60 nm, shell thickness: approximately 10 nm, solid content: 20.5% by mass) manufactured by JGC Catalysts and Chemicals Co., Ltd. The solid silicon oxide particle is propylene glycol monomethyl ether dispersion liquid was prepared using PGM-ST (particle diameter: 10 nm, solid content: 30%) manufactured by Nissan Chemical Industries, Ltd.
[0118] After diluting the solvent displacement liquid 3 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the silicon oxide particles:silica sol ratio was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 4 containing chain silicon oxide particles, hollow silicon oxide particles, and solid silicon oxide particles.
[0119] The obtained coating liquid 4 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.4 µm.
[0120] [Example 5] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 340 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 17:2. Then, an aqueous dispersion of cocoon-shaped silicon oxide particles was added so that the mass ratio of chain silicon oxide particles to cocoon-shaped silicon oxide particles was 17:1. While adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solids concentration reached 30.0 mass% to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 4). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solids concentration 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. The isopropyl alcohol dispersion of hollow silicon oxide particles was prepared using Surulia 4110 (average particle diameter: approximately 60 nm, shell thickness: approximately 10 nm, solid content: 20.5% by mass) manufactured by JGC Catalysts and Chemicals Co., Ltd. The aqueous dispersion of cocoon-shaped silicon oxide particles was prepared using PL-1 (particle diameter: 15 nm, solid content: 12%) manufactured by Fuso Chemical Co., Ltd.
[0121] After diluting the solvent displacement liquid 3 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the silicon oxide particles:silica sol ratio was 25:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 5 containing chain silicon oxide particles, hollow silicon oxide particles, and cocoon-shaped silicon oxide particles.
[0122] The obtained coating liquid 5 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.2 µm.
[0123] [Example 6] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 340 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 17:1. Then, a propylene glycol monomethyl ether dispersion of solid silicon oxide particles was added so that the mass ratio of chain silicon oxide particles to solid silicon oxide particles was 17:2. While adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0% by mass, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 5). Nissan Chemical Industries, Ltd.'s IPA-ST-UP, particle size 40 nm, solid content 15%, was used as the isopropyl alcohol dispersion of chain silicon oxide particles. The hollow silicon oxide particle isopropyl alcohol dispersion liquid was prepared using Surulia 4110 (average particle diameter: approximately 60 nm, shell thickness: approximately 10 nm, solid content: 20.5% by mass) manufactured by JGC Catalysts and Chemicals Co., Ltd. The solid silicon oxide particle is propylene glycol monomethyl ether dispersion liquid was prepared using PGM-ST (particle diameter: 10 nm, solid content: 30%) manufactured by Nissan Chemical Industries, Ltd.
[0124] After diluting the solvent displacement liquid 3 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the silicon oxide particles:silica sol ratio was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 6 containing chain silicon oxide particles, hollow silicon oxide particles, and solid silicon oxide particles.
[0125] The obtained coating liquid 6 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.0 µm.
[0126] [Example 7] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 240 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 3:2. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 6). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter approximately 60 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0127] After diluting the solvent displacement liquid 6 with 3-methoxy-1-butanol to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 7 containing chain silicon oxide particles and hollow silicon oxide particles.
[0128] The obtained coating liquid 7 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.1 µm.
[0129] [Example 8] An aqueous dispersion of cocoon-shaped silicon oxide particles was added to 380 g of an isopropyl alcohol dispersion of chain-shaped silicon oxide particles so that the mass ratio of chain-shaped silicon oxide particles to cocoon-shaped silicon oxide particles was 19:1. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass% to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 7). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain-shaped silicon oxide particles. Fuso Chemical Industries, Ltd.'s PL-1 (particle diameter 15 nm, solid content 12%) was used as the aqueous dispersion of cocoon-shaped silicon oxide particles.
[0130] After diluting the solvent displacement liquid 7 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 8 containing chain silicon oxide particles and cocoon-shaped silicon oxide particles.
[0131] The obtained coating liquid 8 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.1 µm.
[0132] [Example 9] A propylene glycol monomethyl ether dispersion of solid silicon oxide particles was added to 360 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to solid silicon oxide particles was 9:1. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 8). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. Nissan Chemical Industries, Ltd.'s PGM-ST (particle diameter 10 nm, solid content 30%) was used as the propylene glycol monomethyl ether dispersion of solid silicon oxide particles.
[0133] After diluting the solvent displacement liquid 8 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 9 containing chain silicon oxide particles and solid silicon oxide particles.
[0134] The obtained coating liquid 9 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.1 µm.
[0135] [Example 10] A propylene glycol monomethyl ether dispersion of solid silicon oxide particles was added to 320 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to solid silicon oxide particles was 4:1. Then, 1-propoxy-2-propanol was added while the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, and 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 9) was prepared. IPA-ST-UP (particle diameter 40 nm, solid content 15%) manufactured by Nissan Chemical Industries, Ltd. was used as the isopropyl alcohol dispersion of chain silicon oxide particles. PGM-ST (particle diameter 10 nm, solid content 30%) manufactured by Nissan Chemical Industries, Ltd. was used as the propylene glycol monomethyl ether dispersion of solid silicon oxide particles.
[0136] After diluting the solvent displacement liquid 9 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the silicon oxide particles:silica sol ratio was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 10 containing chain silicon oxide particles and solid silicon oxide particles.
[0137] The obtained coating liquid 10 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, and then baked on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer 0. The film thickness was 1.4 µm.
[0138] [Example 11] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 390 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 49:1. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 10). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter approximately 60 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0139] After diluting the solvent displacement liquid 10 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 100:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 11 containing chain silicon oxide particles and hollow silicon oxide particles.
[0140] The obtained coating liquid 11 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, and then baked on a hot plate at 120° C. for 5 minutes to obtain an article having a porous layer 1. The film thickness was 1.2 μm.
[0141] [Example 12] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 390 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 19:1. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 11). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter approximately 60 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0142] After diluting the solvent displacement liquid 11 with 3-methoxy-1-propanol to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 12 containing chain silicon oxide particles and hollow silicon oxide particles.
[0143] The obtained coating liquid 12 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.6 µm.
[0144] [Example 13] After diluting the solvent displacement liquid 11 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the silicon oxide particles:silica sol ratio was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 13 containing chain silicon oxide particles and hollow silicon oxide particles.
[0145] The obtained coating liquid 13 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 2.8 µm.
[0146] [Example 14] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 270 g of a methanol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 9:1. Then, while adding 1-propoxy-2-propanol, the methanol and isopropyl alcohol were heated and distilled. The methanol and isopropyl alcohol were distilled until the solid content reached 30.0 mass %, yielding 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 12). Nissan Chemical Industries, Ltd.'s MA-ST-UP (particle diameter: 40 nm, solid content: 20%) was used as the methanol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter: approximately 60 nm, shell thickness: approximately 10 nm, solid content: 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0147] After diluting the solvent displacement liquid 12 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 14 containing chain silicon oxide particles and hollow silicon oxide particles.
[0148] The obtained coating liquid 14 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.2 µm.
[0149] [Example 15] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 390 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 49:1. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 13). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 1110 (average particle diameter approximately 50 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0150] After diluting the solvent displacement liquid 13 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 100:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 15 containing chain silicon oxide particles and hollow silicon oxide particles.
[0151] The obtained coating liquid 15 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.4 µm.
[0152] [Example 16] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 320 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 4:1. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 14). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 1110 (average particle diameter approximately 50 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0153] After diluting the solvent displacement liquid 14 with 3-methoxy-1-butanol to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 16 containing chain silicon oxide particles and hollow silicon oxide particles.
[0154] The obtained coating liquid 16 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.6 µm.
[0155] [Example 17] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 390 g of a methanol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 49:1. Then, while adding 1-propoxy-2-propanol, the methanol and isopropyl alcohol were heated and distilled. The methanol and isopropyl alcohol were distilled until the solid content reached 30.0 mass %, yielding 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 15). Nissan Chemical Industries, Ltd.'s MA-ST-UP (particle diameter: 40 nm, solid content: 20%) was used as the methanol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter: approximately 60 nm, shell thickness: approximately 10 nm, solid content: 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0156] Solvent displacement liquid 15 was diluted with 3-methoxy-1-butanol to a solids concentration of 20.0% by mass, and then silica sol 1 was added thereto so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 17 containing chain silicon oxide particles and hollow silicon oxide particles.
[0157] The obtained coating liquid 17 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 2.1 µm.
[0158] [Example 18] An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 360 g of a methanol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 9:1. Then, while adding 1-propoxy-2-propanol, the methanol and isopropyl alcohol were heated and distilled. The methanol and isopropyl alcohol were distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 16). MA-ST-UP (particle diameter 40 nm, solid content 20%) manufactured by Nissan Chemical Industries, Ltd. was used as the methanol dispersion of chain silicon oxide particles. Surulia 4110 (average particle diameter approximately 60 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) manufactured by JGC Catalysts and Chemicals, Ltd. was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0159] After diluting the solvent displacement liquid 16 with 3-methoxy-1-butanol to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 18 containing chain silicon oxide particles and hollow silicon oxide particles.
[0160] The obtained coating liquid 18 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater. After that, the film was baked on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer containing particles. The film thickness was 1.5 µm.
[0161] [Comparative Example 1] 1-propoxy-2-propanol was added to 440 g of an isopropyl alcohol dispersion of hollow silicon oxide particles, while the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 300 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 17). JGC Catalysts and Chemicals' Sururia 4110 (average particle size: approximately 60 nm, shell thickness: approximately 10 nm, solid content: 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0162] After diluting the solvent displacement liquid 17 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 100:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 19 containing hollow silicon oxide particles.
[0163] The obtained coating liquid 19 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater. After that, the film was baked on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer containing particles. The film thickness was 1.4 µm.
[0164] Comparative Example 2 1-propoxy-2-propanol was added to 400 g of an isopropyl alcohol dispersion of chain silicon oxide particles (IPA-ST-UP, manufactured by Nissan Chemical Industries, Ltd., particle size 40 nm, solids concentration 15%), while the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solids concentration reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 18).
[0165] After diluting the solvent displacement liquid 18 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 25:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 20 containing chain silicon oxide particles.
[0166] The obtained coating liquid 20 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.5 µm.
[0167] Comparative Example 3 1-propoxy-2-propanol and ethyl lactate were added in a ratio of 7:3 to a propylene glycol monomethyl ether dispersion of solid silicon oxide particles so that the solid content concentration was 20.0 mass %, to obtain Dispersion 3. PGM-ST (particle diameter 10 nm, solid content concentration 30%) manufactured by Nissan Chemical Industries, Ltd. was used as the propylene glycol monomethyl ether dispersion of solid silicon oxide particles.
[0168] Silica sol 1 was added to dispersion liquid 3 so that the silicon oxide particles:silica sol component ratio was 25:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain coating liquid 21 containing solid silicon oxide particles.
[0169] The obtained coating liquid 21 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.0 µm.
[0170] Comparative Example 4 An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 80 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 1:4. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 19). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter approximately 60 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0171] After diluting the solvent displacement liquid 19 with 1-ethoxy-2-propanol to a solids concentration of 20.0% by mass, silica sol 1 was added so that the ratio of silicon oxide particles to silica sol components was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 22 containing chain silicon oxide particles and hollow silicon oxide particles.
[0172] The obtained coating liquid 22 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.6 µm.
[0173] Comparative Example 5 An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 40 g of a methanol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 1:9. Then, while adding 1-propoxy-2-propanol, the methanol and isopropyl alcohol were heated and distilled. The methanol and isopropyl alcohol were distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 20). Nissan Chemical Industries, Ltd.'s MA-ST-UP (particle diameter 40 nm, solid content 20%) was used as the methanol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 1110 (average particle diameter approximately 50 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0174] After diluting the solvent displacement liquid 20 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the silicon oxide particles:silica sol ratio was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 23 containing chain silicon oxide particles and hollow silicon oxide particles.
[0175] The obtained coating liquid 23 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater. After that, the film was baked on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer containing particles. The film thickness was 1.5 µm.
[0176] Comparative Example 6 An isopropyl alcohol dispersion of hollow silicon oxide particles was added to 20 g of an isopropyl alcohol dispersion of chain silicon oxide particles so that the mass ratio of chain silicon oxide particles to hollow silicon oxide particles was 1:19. Then, while adding 1-propoxy-2-propanol, the isopropyl alcohol was heated and distilled. The isopropyl alcohol was distilled until the solid content reached 30.0 mass %, to prepare 200 g of a 1P2P solvent displacement solution of silicon oxide particles (hereinafter referred to as solvent displacement solution 21). Nissan Chemical Industries, Ltd.'s IPA-ST-UP (particle diameter 40 nm, solid content 15%) was used as the isopropyl alcohol dispersion of chain silicon oxide particles. JGC Catalysts and Chemicals Co., Ltd.'s Surulia 4110 (average particle diameter approximately 60 nm, shell thickness approximately 10 nm, solid content 20.5 mass %) was used as the isopropyl alcohol dispersion of hollow silicon oxide particles.
[0177] After diluting the solvent displacement liquid 19 with ethyl lactate to a solids concentration of 20.0% by mass, silica sol 1 was added so that the silicon oxide particles:silica sol ratio was 50:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain a coating liquid 24 containing chain silicon oxide particles and hollow silicon oxide particles.
[0178] The obtained coating liquid 24 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.6 µm.
[0179] Comparative Example 7 The propylene glycol monomethyl ether dispersion of chain silicon oxide particles was mixed with the propylene glycol monomethyl ether dispersion of solid silicon oxide particles at a ratio of 7:3, to obtain dispersion 4.
[0180] Propylene glycol monomethyl ether was added to Dispersion Liquid 4 to achieve a solids concentration of 20.0%, followed by Silica Sol 1 to achieve a silicon oxide particle:silica sol ratio of 25:1. The mixture was further mixed and stirred at room temperature for 2 hours to obtain Coating Liquid 25 containing solid silicon oxide particles. Nissan Chemical Co., Ltd.'s PGM-ST-UP (particle diameter 40 nm, solids concentration 15%) was used as a propylene glycol monomethyl ether dispersion of chain silicon oxide particles. Nissan Chemical Co., Ltd.'s PGM-ST (particle diameter 10 nm, solids concentration 30%) was used as a propylene glycol monomethyl ether dispersion of solid silicon oxide particles.
[0181] The obtained coating liquid 25 was dropped onto a glass substrate and a silicon wafer, and a film was formed using a spin coater, followed by baking on a hot plate at 120°C for 5 minutes to obtain an article having a porous layer. The film thickness was 1.9 µm.
[0182] The mixing ratio of the chain particles to the non-chain particles contained in the inorganic particles and the evaluation results of the film properties for Examples 1 to 18 and Comparative Examples 1 to 7 are summarized in Table 1. For simplicity, in Table 1, the region closer to the substrate than half the thickness of the porous layer 120 is referred to as the lower layer, and the region farther from the substrate than half the thickness is referred to as the upper layer.
[0183] [Table 1]
[0184] The results in Table 1 show that in Examples 1 to 18, in which the inorganic particles contained both chain particles and particles other than chain particles and the volume ratio of the chain particles to the inorganic particles was in the range of 55% to 95%, a crack-free porous layer was achieved even when the film thickness was 1.0 μm or more. It was also confirmed that the resulting porous layer was a low-refractive index film with a refractive index of 1.3 or less.
[0185] In Comparative Examples 1 to 6, in which the ratio of chain particles to inorganic particles was outside the range of 55% or more and 95% or less, cracks occurred even when the refractive index difference between the region closer to the substrate than half the thickness of the porous layer 120 and the region farther from the substrate than half the thickness of the porous layer 120 was 0.01 or less.
[0186] In Comparative Example 7, the inorganic particles include chain particles and particles other than chain particles, and the volume ratio of the chain particles to the inorganic particles is in the range of 55% to 95%. The coating liquid does not include a water-soluble solvent having a hydroxyl group with 4 to 6 carbon atoms, which accounts for 30% to 80% by mass of the solvent. Therefore, the refractive index difference between the region closer to the substrate than halfway through the film thickness of the porous layer 120 and the region farther from the substrate than halfway through the film thickness exceeded 0.01, causing cracks. It is believed that the large difference in refractive index within the film caused stress to be applied to areas with film density differences, resulting in cracks.
[0187] (Configuration 1) An article comprising a substrate and a porous layer provided on the substrate, the porous layer including a plurality of inorganic particles bound together by an inorganic binder, An article characterized in that the plurality of inorganic particles include chain particles and particles other than the chain particles, and the volume ratio of the chain particles to the plurality of inorganic particles is 55% or more and 95% or less.
[0188] (Configuration 2) 2. The article according to claim 1, wherein the plurality of inorganic particles include at least one type of particles selected from the group consisting of hollow particles, cocoon-shaped particles, and solid particles other than the chain particles.
[0189] (Configuration 3) 3. The article according to claim 1 or 2, wherein the plurality of inorganic particles includes hollow particles as particles other than the chain particles.
[0190] (Configuration 4) 4. The article according to any one of claims 1 to 3, wherein the plurality of inorganic particles include at least one type of particle selected from the group consisting of silicon oxide, magnesium fluoride, lithium fluoride, calcium fluoride, and barium fluoride.
[0191] (Configuration 5) 5. The article according to any one of claims 1 to 4, wherein the plurality of inorganic particles are silicon oxide particles.
[0192] (Configuration 6) 6. The article of claim 5, wherein the inorganic binder is a silicon oxide compound.
[0193] (Configuration 7) The article according to any one of configurations 1 to 6, wherein the thickness of the porous layer is 300 nm or more and 5000 nm or less.
[0194] (Configuration 8) An article described in any one of structures 1 to 7, characterized in that the difference in refractive index between the region closer to the substrate than half the thickness of the porous layer 120 and the region farther from the substrate than half the thickness of the porous layer 120 is 0.01 or less.
[0195] (Configuration 9) 9. The article according to any one of claims 1 to 8, wherein the refractive index of the porous layer is 1.15 or more and 1.30 or less.
[0196] (Configuration 10) The article according to any one of configurations 1 to 9, further comprising an intermediate layer between the substrate and the porous layer.
[0197] (Configuration 11) 11. The article according to claim 10, wherein the intermediate layer is a laminate of a plurality of inorganic compound layers or a polymer layer having an uneven surface.
[0198] (Configuration 12) 12. The article according to any one of claims 1 to 11, further comprising a functional layer on the surface of the porous layer opposite to the substrate.
[0199] (Configuration 13) 13. The article according to claim 12, wherein the functional layer is a layer containing a polymer having amphoteric hydrophilic groups.
[0200] (Configuration 14) 13. The article according to claim 12, wherein the functional layer is any one of a layer containing a fluoropolymer, a fluorosilane monolayer, and a layer containing titanium oxide particles.
[0201] (Configuration 15) 10. The article according to any one of claims 1 to 9, wherein the substrate has a photoelectric conversion section and a microlens array, and the porous layer has a light-transmitting plate on the surface opposite to the substrate.
[0202] (Configuration 16) 16. The article according to claim 15, wherein the refractive index of the porous layer is lower than the refractive index of the microlenses that make up the microlens array.
[0203] (Configuration 17) 17. The article according to claim 15 or 16, wherein the porous layer has a thickness of 300 nm to 5000 nm.
[0204] (Configuration 18) 18. The article according to any one of claims 15 to 17, wherein the thickness of the porous layer is at least twice the height difference of the concave and convex portions of the microlens array.
[0205] (Configuration 19) 19. The article of any one of claims 15 to 18, further comprising an anti-reflection layer between the porous layer and the microlens array.
[0206] (Configuration 20) An imaging device comprising: a housing; an optical system formed of a plurality of lenses within the housing; and an imaging element that receives light that has passed through the optical system, An imaging device, wherein at least one of the plurality of lenses is the article described in any one of configurations 1 to 14.
[0207] (Configuration 21) An imaging device comprising: a housing; an optical system formed of a plurality of lenses within the housing; and an imaging element that receives light that has passed through the optical system, 20. An imaging device characterized in that the imaging element is the article described in any one of configurations 15 to 19.
[0208] (Configuration 22) A coating liquid containing a plurality of inorganic particles, a component that serves as an inorganic binder, and an organic solvent, the plurality of inorganic particles include chain particles and particles other than the chain particles, and the volume ratio of the chain particles to the plurality of inorganic particles is 55% or more and 95% or less; A coating liquid, characterized in that 30% by mass or more and 80% by mass or less of the organic solvent is a water-soluble solvent having a hydroxyl group having 4 to 6 carbon atoms.
[0209] (Configuration 23) 23. The coating solution according to claim 22, wherein the water-soluble solvent having a hydroxyl group and having from 4 to 6 carbon atoms contains at least one selected from the group consisting of ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, 1-ethoxy-2-propanol, ethyl lactate, and 3-methoxy-1-butanol.
[0210] (Configuration 24) The chain particles are secondary particles formed by bonding a plurality of primary particles together, 24. The coating fluid according to aspect 22 or 23, wherein the average particle size of the chain particles is 3 to 10 times the average particle size of the primary particles.
[0211] (Configuration 25) 25. The coating fluid according to claim 24, wherein the average particle size of the primary particles is 8 nm or more and 20 nm or less.
[0212] (Configuration 26) 26. The coating solution according to any one of aspects 22 to 25, wherein the particles other than the chain particles include at least one selected from the group consisting of solid particles, hollow particles, cocoon-shaped particles, and solid particles.
[0213] (Configuration 27) 27. The coating fluid according to any one of aspects 22 to 26, wherein the particles other than the chain particles are hollow particles having an average particle diameter of 15 nm or more and 300 nm or less.
[0214] (Configuration 28) 28. The coating solution according to any one of claims 22 to 27, wherein the plurality of inorganic particles include at least one type of particle selected from the group consisting of silicon oxide, magnesium fluoride, lithium fluoride, calcium fluoride, and barium fluoride.
[0215] (Configuration 29) 29. The coating fluid according to any one of aspects 22 to 28, wherein the inorganic particles are silicon oxide particles, and the component serving as the inorganic binder is a silicon oxide compound.
[0216] (Configuration 30) A coating liquid according to any one of configurations 22 to 2, characterized in that the content of the component that becomes the inorganic binder is 0.2 parts by mass or more and 20 parts by mass or less based on the solid components contained in the coating liquid.
[0217] (Configuration 31) The method includes a step of applying a coating liquid onto a substrate, and a step of drying and / or baking the substrate on which the coating liquid has been applied, A method for producing an article, wherein the coating liquid is the coating liquid described in any one of Configurations 22 to 30. [Explanation of symbols]
[0218] 100 goods 10 Base material 20 Porous layer 21 Chain particles 22 Particles other than chain particles 24 Inorganic binder 25 void
Claims
1. An article comprising a substrate and a porous layer provided on the substrate, the porous layer including a plurality of inorganic particles bound together by an inorganic binder, An article characterized in that the plurality of inorganic particles include chain particles and particles other than the chain particles, and a volume ratio of the chain particles to the plurality of inorganic particles is 55% or more and 95% or less.
2. 2. The article according to claim 1, wherein the plurality of inorganic particles includes at least one type of particle selected from the group consisting of hollow particles, cocoon-shaped particles, and solid particles as particles other than the chain-like particles.
3. 3. The article according to claim 2, wherein the plurality of inorganic particles includes hollow particles as particles other than the chain particles.
4. 2. The article of claim 1, wherein the plurality of inorganic particles comprises at least one type of particles selected from the group consisting of silicon oxide, magnesium fluoride, lithium fluoride, calcium fluoride, and barium fluoride.
5. 2. The article of claim 1, wherein the plurality of inorganic particles are silicon oxide particles.
6. 6. The article of claim 5, wherein the inorganic binder is a silicon oxide compound.
7. 2. The article according to claim 1, wherein the porous layer has a thickness of 300 nm or more and 5000 nm or less.
8. The article according to claim 1, characterized in that the difference in refractive index between a region of the porous layer 120 closer to the substrate than half the thickness of the film and a region of the porous layer 120 farther from the substrate than half the thickness of the film is 0.01 or less.
9. 2. The article according to claim 1, wherein the refractive index of the porous layer is 1.15 or more and 1.30 or less.
10. The article of claim 1 further comprising an intermediate layer between the substrate and the porous layer.
11. 11. The article according to claim 10, wherein the intermediate layer is a laminate of a plurality of inorganic compound layers or a polymer layer having an uneven surface.
12. The article according to claim 1 , further comprising a functional layer on the surface of the porous layer opposite the substrate.
13. The article according to claim 12, wherein the functional layer is a layer containing a polymer having amphoteric hydrophilic groups.
14. The article according to claim 12, wherein the functional layer is any one of a layer containing a fluoropolymer, a fluorosilane monolayer, and a layer containing titanium oxide particles.
15. The article according to claim 1 , wherein the substrate has a photoelectric conversion portion and a microlens array, and the porous layer has a light-transmitting plate on a surface opposite to the substrate.
16. 16. The article of claim 15, wherein the refractive index of the porous layer is lower than the refractive index of the microlenses that make up the microlens array.
17. The article according to claim 15, wherein the porous layer has a thickness of 300 nm to 5000 nm.
18. 16. The article according to claim 15, wherein the thickness of the porous layer is at least twice the height difference of the projections and recesses of the microlens array.
19. 16. The article of claim 15, further comprising an anti-reflective layer between the porous layer and the microlens array.
20. An imaging device comprising: a housing; an optical system including a plurality of lenses disposed within the housing; and an imaging element that receives light that has passed through the optical system, An imaging device, characterized in that at least one of the plurality of lenses is an article according to any one of claims 1 to 14.
21. An imaging device comprising: a housing; an optical system including a plurality of lenses disposed within the housing; and an imaging element that receives light that has passed through the optical system, An imaging device, wherein the imaging element is the article according to any one of claims 15 to 19.
22. A coating liquid comprising a plurality of inorganic particles, a component serving as an inorganic binder, and an organic solvent, the plurality of inorganic particles include chain particles and particles other than the chain particles, and a volume ratio of the chain particles to the plurality of inorganic particles is 55% or more and 95% or less; A coating liquid, characterized in that 30% by mass or more and 80% by mass or less of the organic solvent is a water-soluble solvent having a hydroxyl group having 4 to 6 carbon atoms.
23. The coating fluid according to claim 22, characterized in that the water-soluble solvent having a hydroxyl group having from 4 to 6 carbon atoms contains at least one selected from the group consisting of ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, 1-ethoxy-2-propanol, ethyl lactate, and 3-methoxy-1-butanol.
24. The chain particles are secondary particles formed by bonding a plurality of primary particles together, 23. The coating fluid according to claim 22, wherein the average particle size of the chain particles is 3 to 10 times the average particle size of the primary particles.
25. 25. The coating fluid according to claim 24, wherein the average particle size of the primary particles is 8 nm or more and 20 nm or less.
26. The coating fluid according to claim 22, characterized in that the particles other than the chain particles include at least one type selected from the group consisting of solid particles, hollow particles, cocoon-shaped particles and solid particles.
27. 23. The coating fluid according to claim 22, further comprising hollow particles having an average particle diameter of 15 nm or more and 300 nm or less as particles other than the chain particles.
28. 23. The coating fluid according to claim 22, wherein the plurality of inorganic particles include at least one type of particles selected from the group consisting of silicon oxide, magnesium fluoride, lithium fluoride, calcium fluoride, and barium fluoride.
29. 23. The coating fluid according to claim 22, wherein the inorganic particles are silicon oxide particles, and the component serving as the inorganic binder is a silicon oxide compound.
30. 23. The coating fluid according to claim 22, wherein the content of the component that becomes the inorganic binder is 0.2 parts by mass or more and 20 parts by mass or less based on the solid components contained in the coating fluid.
31. The method includes a step of applying a coating liquid onto a substrate, and a step of drying and / or baking the substrate on which the coating liquid has been applied, A method for producing an article, comprising the step of: applying a coating liquid to the article;
32. An optical device comprising a housing and an optical system including a plurality of lenses disposed within the housing, 15. An optical instrument, wherein at least one of the plurality of lenses is an article according to any one of claims 1 to 14.